Elastic-plastic Transition of a Non-homogeneous Thick-walled Circular Cylinder under Internal Pressure - Sharma, Sanjeev (Defence Science Journal, 2004)
Elastic-plastic stresses have been derived for a cylinder under internal pressure using Seth's transition theory. The effect of non-homogeneity has been discu ssed numerically and depicted graphically. It has been observed that a cylinder made of non-homogeneous material with nohomogeneity increasing radially requires a higher percentage increase in pressure to become fully plastic than to its initial yielding as compared to a homogeneous cylinder and is on the safer side of the design.